Aplikasi “Golek Tukang” untuk Pencarian Jasa Perbaikan Rumah di Daerah Surabaya Berbasis Android - Andreas Endrahadi Wijaksono; Henry Novianus Palit; Anita Nathania Purbowo (Jurnal Infra, 2019)
In the reality of life today, many people have smartphones connected to the internet. This condition causes an increase in information needs through gadgets. One of them is to search for home improvement services / builders online through the application on the smartphone. But in the Surabaya area to find a handyman, they still use a manual system with the principle of finding information on builders through the website or by word of mouth so that the people of Surabaya do not meet the appropriate home improvement needs.With that problem, the Android Golek Tukang application will be created to find home repair services. The feature provided in the "Golek Tukang" application is service seekers can choose the appropriate service provider, there is a price negotiation feature to provide convenience to each party, a chat feature that makes it easier for service seekers and service providers to communicate, and the maps feature by which service providers can easily find out the location service seekers.This Android “Golek Tukang” application enables many people of Surabaya to find home repair services easily, quickly, and comfortably. With this application, also enables service providers easily get jobs without having to use a manual system. This application is created using the programming language PHP and Java, the database used is MySQL, and the library used is Retrofit.